2020
DOI: 10.3389/fnhum.2020.00330
|View full text |Cite
|
Sign up to set email alerts
|

Functional Alterations in Resting-State Visual Networks in High-Tension Glaucoma: An Independent Component Analysis

Abstract: Background: High-tension glaucoma (HTG) is the most common type of primary open angle glaucoma and elevated intraocular pressure (IOP) is the major risk factor of the disease. The aim of this study was to assess alterations in resting-state visual networks in patients with HTG and investigate the effect of elevated IOP on the visual networks. Methods: T1-weighted and resting-state functional MRI images were acquired from 36 HTG patients (aged 49.22 ± 15.26 years) and 20 healthy controls (aged 49.90 ± 5.62 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The occipital cortex is well known to be responsible for visual processing, mainly associated with visual formation and visual perception activities ( Yu et al, 2017 ). Specifically, CAL is the seat of primary visual cortex (V1) which receives direct visual inputs from the eyes via thalamic relays ( Lu et al, 2019 ), LG is within the visual recognition network involved in encoding visual memories ( Mao et al, 2020 ; Wang et al, 2020 ), and MOG is part of the dorsal visual areas which also plays a role in processing visual perception ( Tu et al, 2013 ; Shao et al, 2019 ). Reduced VMHC in these regions have been reported in glaucoma ( Wang et al, 2018 ), amblyopia ( Liang et al, 2017 ), blindness ( Shao et al, 2018 ), and globe injury ( Ye et al, 2018 ), consistently interpreted as disturbed interhemispheric functional synchronization in visual cortices.…”
Section: Discussionmentioning
confidence: 99%
“…The occipital cortex is well known to be responsible for visual processing, mainly associated with visual formation and visual perception activities ( Yu et al, 2017 ). Specifically, CAL is the seat of primary visual cortex (V1) which receives direct visual inputs from the eyes via thalamic relays ( Lu et al, 2019 ), LG is within the visual recognition network involved in encoding visual memories ( Mao et al, 2020 ; Wang et al, 2020 ), and MOG is part of the dorsal visual areas which also plays a role in processing visual perception ( Tu et al, 2013 ; Shao et al, 2019 ). Reduced VMHC in these regions have been reported in glaucoma ( Wang et al, 2018 ), amblyopia ( Liang et al, 2017 ), blindness ( Shao et al, 2018 ), and globe injury ( Ye et al, 2018 ), consistently interpreted as disturbed interhemispheric functional synchronization in visual cortices.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma is caused by diabetes mellitus, aging, black ethnicity, and family history, but the most important modifiable risk factor is elevated intraocular pressure (IOP). The most common type of glaucoma-inducing irreversible blindness, high-tension primary open angle glaucoma (HTPOAG), is described by an IOP > 21 mmHg and an open angle of the anterior chamber of the eye [1].…”
Section: Ali Mohamed Ali Ismailmentioning
confidence: 99%
“…Structural changes were observed in several studies that compared glaucoma participants to healthy controls, showing altered white matter tracts and gray matter atrophy in brain areas involved in visual processing (Chen et al, 2013 ; Frezzotti et al, 2014 ; Wang et al, 2016a ; Giorgio et al, 2018 ). Moreover, several functional magnetic resonance imaging (fMRI) studies have shown altered cortical activity in glaucoma patients (Qing et al, 2010 ; Gerente et al, 2015 ; Jiang et al, 2017 ; Wang et al, 2020 ). It is largely unknown how these anatomical and functional changes affect the integrity of cortical functional networks and how, in turn, changes in these networks affect visual functioning of patients.…”
Section: Introductionmentioning
confidence: 99%